Plant controls on Late Quaternary whole ecosystem structure and function - Jeffers, ES; Whitehouse, NJ; Lister, A; Plunkett, G; Barratt, P; Smyth, E; Lamb, P; Dee, MD; Brooks, SJ; Willis, KJ; Froyd, CA; Watson, JE; et al. (Wiley, 2018)
Plants and animals influence biomass production and nutrient cycling in terrestrial ecosystems; however their relative importance remains unclear. We assessed the extent to which mega-herbivore species controlled plant community composition and nutrient cycling, relative to other factors during and after the Late Quaternary extinction event in Britain and Ireland, when two-thirds of the region’s mega-herbivore species went extinct. Warmer temperatures, plant-soil and plant-plant interactions, and reduced burning contributed to the expansion of woody plants and declining nitrogen availability in our five study ecosystems. Shrub biomass in particular was consistently one of the strongest predictors of ecosystem change, equaling or exceeding the effects of other biotic and abiotic factors. In contrast, there was relatively little evidence for mega-herbivore control on plant community composition and nitrogen availability. The ability of plants to determine the fate of terrestrial ecosystems during periods of global environmental change may therefore be greater than previously thought.